Nigerian Christian Drama: A Reconstruction of History - Edebor, Solomon (Àgídìgbo: ABUAD Journal of the Humanities, 2016)
This paper examines the history and development of Nigerian Christian drama from its earliest time till date. The paper affirms Agoro 's position on the continuation of theatre in the Church after the exit of Hubert Ogunde contrary to Adedeji's submission, but notes the negative impacts of his untimely departure. Besides, the paper shows the factors responsible for the emergence of independent Christian drama groups, and generally indicates a particular trend in terms of changes in the role of Christian drama at different phases of its development in Nigeria. The study concludes that although Christian productions are making significant impacts in the society today, efforts still have to be concentrated on scripting, and productions that can fill and sustain the theatre.